2017
DOI: 10.9790/4861-0901033844
|View full text |Cite
|
Sign up to set email alerts
|

Growth, characterization, and antibacterial studies of L-Lysine single crystals added with potassium bromide

Abstract: Single crystals of L-lysine added

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…This LIP crystal is formed by adding Lisoleucine picric acid (1:1) [21]. L-lysine-doped KDP crystals are found to be more beneficial from an application point of view as compared to pure KDP crystals as it was revealed that dielectric constant and the dielectric loss of L-lysine-doped KDP crystals were lower than the pure KDP crystals [22] .Apart from physics point of view, antibacterial studies of L-Lysine single crystals added with potassium bromide were studied out [23] .It was experimental that as compared to L-Lysine, the grown LYPB crystals show a moderate activity against the selected strains of microorganisms in following order as Staphylococcus aureus>Lactobacillus >Escherichia coli >Salmonella typhi >Bacillus subtitlis. Hence the grown LYPB crystals may be considered for pharmacological applications.…”
Section: Introductionmentioning
confidence: 99%
“…This LIP crystal is formed by adding Lisoleucine picric acid (1:1) [21]. L-lysine-doped KDP crystals are found to be more beneficial from an application point of view as compared to pure KDP crystals as it was revealed that dielectric constant and the dielectric loss of L-lysine-doped KDP crystals were lower than the pure KDP crystals [22] .Apart from physics point of view, antibacterial studies of L-Lysine single crystals added with potassium bromide were studied out [23] .It was experimental that as compared to L-Lysine, the grown LYPB crystals show a moderate activity against the selected strains of microorganisms in following order as Staphylococcus aureus>Lactobacillus >Escherichia coli >Salmonella typhi >Bacillus subtitlis. Hence the grown LYPB crystals may be considered for pharmacological applications.…”
Section: Introductionmentioning
confidence: 99%